Deep margin elevation in anterior teeth: A clinical report - Grassi, Elisa D.A. [UNESP]; Gresnigt, Marco M.M. (Elsevier, 2025)
Subgingival fractures in the anterior region present challenges for adhesive ceramic restorations. The deep margin elevation (DME) technique, using composite resin to elevate subgingival margins before indirect restoration preparation, has been reported to improve outcomes while maintaining esthetic and functional integrity. Developed for posterior teeth, DME aligns with minimally invasive principles and leverages adhesive material advancements. Its use in anterior teeth preserves gingival architecture, supports periodontal health, and ensures precise adhesive protocols, essential for successful rehabilitation. This report outlines DME's systematic application for managing anterior subgingival fractures.